1981
DOI: 10.1346/ccmn.1981.0290308
|View full text |Cite
|
Sign up to set email alerts
|

Role of Manganese in the Oxidation of Arsenite by Freshwater Lake Sediments

Abstract: The importance of various sediment components in the oxidation of As(III) (arsenite) to As(V) (arsenate) by freshwater lake sediments in southern Saskatchewan was examined. Treating the sediments with hydroxylamine hydrochloride or sodium acetate to remove Mn greatly decreased the oxidation of As(III). Furthermore, synthetic Mn(IV) oxide was a very effective oxidant with respect to As(liD: 216 t~g As(V)/ml was formed in solution when 1000 txg As(III)/ml was added to suspensions of 0.1 g of the oxide. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 16 publications
1
55
1
2
Order By: Relevance
“…Oscarson et al (23) found that As(III) oxidation rate increased and reached a maximum as the amount of As(III) was increased at a fixed MnO2 suspension density. It was postulated that a barrier was formed at or near the surface of the oxide that prevented further reduction of the structural Mn(IV) in the interior of crystallites (23). This is consistent with our results, which suggest that a surface layer of covalently bound As(V) forms on the reacted MnO2 surface which would limit further reaction of MnO2 with As(III).…”
Section: Resultsmentioning
confidence: 99%
“…Oscarson et al (23) found that As(III) oxidation rate increased and reached a maximum as the amount of As(III) was increased at a fixed MnO2 suspension density. It was postulated that a barrier was formed at or near the surface of the oxide that prevented further reduction of the structural Mn(IV) in the interior of crystallites (23). This is consistent with our results, which suggest that a surface layer of covalently bound As(V) forms on the reacted MnO2 surface which would limit further reaction of MnO2 with As(III).…”
Section: Resultsmentioning
confidence: 99%
“…As the reaction time increases, the oxidized fraction of As(III) in solution not removed by IMCS(7:3) is slightly increased, likely due to the presence of manganese oxide on the surface of IMCS(7:3). 38 Adsorption Isotherm of Phosphate and Arsenic. Adsorption isotherms of phosphate onto ICS, MCS, and IMCS(7:3) were obtained at pH 4.5 and 7 and at constant ionic strength (0.01 M NaNO 3 ) as shown in Figure 8a and b. MCS shows the least removal capacity for phosphate.…”
Section: Removal Of As(iii) By Ics Mcs and Imcs In A Batchmentioning
confidence: 99%
“…Mn oxides are common soil minerals with a high capacity to oxidize heavy metals and metalloids including As(III) (Post 1999). The effective oxidation of As (III) by synthetic Mn oxides such as birnessite (δ-MnO 2 ) has been reported (Oscarson et al 1981(Oscarson et al , 1983. However, 4…”
Section: Solid Phase Analysismentioning
confidence: 99%